Avaliação de desempenho organizacional: um estudo aplicado em hospitais filantrópicos - Carneiro da Cunha, Julio Araujo [UNESP]; Correa, Hamilton Luiz (Fundação Getúlio Vargas (FGV), 2013)
An evaluation of organizational performance requires studies that encompass the specificities of the object under analysis, which is valid for health organizations. However, this type of organization has little support from Administration techniques and knowledge, thus generating deficiencies in management and control. As a result, the objective of this article is to develop a model for evaluating the specific performance of philanthropic hospitals and to compare the efficiency of those organizations. A theoretical model was createdand subsequently validated by specialists. A data envelopment analysis was conducted by means ofusing the data from 70 hospitals, collected in afield research. The conclusion is that there is no great availability of managerial information in Brazilian hospitals, and elements were pointed out for increasing sample efficiency.
Evaluation of organizational performance: an study applied in philanthropic hospitals
Evaluación de desempeño organizacional: un estudio aplicado en hospitales filantrópicos
Keywords: Hospitals; philanthropy; performance evaluation; efficiency; DEA